Evaluation of the nutritional status in pre-school and school children, Madeira Island, Portugal - Ferreira, Mafalda (2019)
In order to evaluate the nutritional status of Câmara dos Lobos Municipality students, all pre-primary and primary public schools located in the municipality were contacted. The assessment of height and body weight, used to calculate body mass index as a method of diagnosing low weight, overweight, or obesity, was performed in 1405 students aged 3 to 9 years. The cut-off points of the BMI adopted by the IOTF were used to calculate the prevalence of underweight, overweight and obesity. The prevalence of underweight, overweight and obesity was 2.5%, 36.9% and 13.1%, respectively. In children between the ages of 3 and 5 the prevalence of overweight (including obesity) is 6.9-12.8% in boys and 6.9- 9.8% in girls. Six-year-olds had a higher prevalence of overweight when compared to other children. Students from the schools of the Estreito community in Câmara de Lobos presented the highest prevalence of low weight (3.5%). Students from the community of Curral das Freiras presented a higher prevalence of overweight (42.0%), and the prevalence of obesity was 21.0%. In order to prevent childhood obesity the municipality of Câmara de Lobos might consider these results for appropriate action.